2021
DOI: 10.1111/ijac.13748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiC nanowhisker addition on microstructure and mechanical properties of regenerated cemented carbides by low‐pressure sintering

Abstract: Cemented carbide, as an important industrial material, is well-known as "industrial teeth" due to its high hardness, strength, wear resistance, and other fantastic properties, which plays an important role in the fields of petroleum machinery, mining machinery, and mechanical processing. [1][2][3] However, there is a shortage of tungsten (W) and cobalt (Co) resources, which are main raw materials for cemented carbide. Therefore, recycling waste-cemented carbide to prepare regenerated cemented carbide raw mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Comparing the phases of cermets with different content of SiCw, it is found that the peak of cermets added with SiCw shifts to the right, indicating that the diffraction angle increases and the lattice constant decreases. The reason is that the radius of Si atom is smaller than that of Mo atom and Ni atom, which causes lattice distortion in Mo 2 NiB 2 , and increases the internal energy and internal stress of the material 15 . Then, when the load is applied, the dislocation slip deformation will be hindered.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparing the phases of cermets with different content of SiCw, it is found that the peak of cermets added with SiCw shifts to the right, indicating that the diffraction angle increases and the lattice constant decreases. The reason is that the radius of Si atom is smaller than that of Mo atom and Ni atom, which causes lattice distortion in Mo 2 NiB 2 , and increases the internal energy and internal stress of the material 15 . Then, when the load is applied, the dislocation slip deformation will be hindered.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5C shows that when the whisker content is 0.5 wt%, the grain distribution of cermets is the most uniform, in which 1–3 μm grains are the most, and SiCw is uniformly dispersed in cermets. Grain refinement is mainly due to the fact that the dissolved SiCw in the binder phase reduces the supersaturation of the binder phase relative to the hard phase, and reduces the driving force of the hard phase during the dissolution and precipitation of the binder phase 15 . SiCw distributed at the grain boundary inhibits the dissolution of the hard phase in the binder phase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations